Parents' Perspectives Toward School Reopening During COVID-19 Pandemic in Indonesia—A National Survey - Pudjiadi, Antonius Hocky; Putri, Nina Dwi; Sjakti, Hikari Ambara; Yanuarso, Piprim Basarah; Gunardi, Hartono; Roeslani, Rosalina Dewi; Pasaribu, Ade Djanwardi; Nurmalia, Lies Dewi; Sambo, Catharine Mayung; Habibah, Lathiefatul; Utami, Indriyanti Natasya Ayu; Prawira, Yogi; et al. (Frontiers in Public Health, 2022)
Background All sectors are affected due to COVID-19 pandemic occurring worldwide, including the education industry. School closure had been taking place for more than a year in Indonesia. Despite the controversies, Indonesian government had decided to begin school reopening. Objectives This study aims to assess parental readiness for school reopening, and factors affecting parental attitude toward school reopening. Methods A cross-sectional study using online questionnaire distributed via official Indonesian Pediatric Society (IPS) official social media account collected between March and April 2021. The questionnaire contained the general characteristics of study participants, parents' knowledge, and perspectives on COVID-19, and health protocols for school reopening. Results A total of 17,562 responses were collected, of which 55.7% parents were ready to send their children to school should school reopens. Factors significantly contribute to parental decision to keep their child at home were: presence of vulnerable population at home [OR = 1.18 (1.10–1.27), p < 0.001], children with comorbidities [OR = 2.56 (2.29–2.87), p < 0.001], perception of COVID-19 as a dangerous disease [OR = 28.87 (14.29–58.33), p < 0.001], experience with COVID-19 positive cases in the community [OR = 1.75 (1.61–1.90), p < 0.001], COVID-19 related death in the community [OR = 2.05 (1.90–2.21), P < 0.001], approval for adult COVID-19 vaccination [OR = 1.69 (1.53–1.87), p < 0.001], and ownership of private transportation [OR = 1.46 (1.30–1.66), p <0.001]. Conclusion We identified several factors affecting parental perception on school reopening during COVID-19 pandemic that should be addressed. This study can be used for policy-maker to make further recommendations and health educations prior to school reopening in Indonesia.